The low-cost technical system of rural sustainable wood construction and its suitability based on the small-diameter round timber of fast-growing Northeast Larch - Ying Wu; Hongpeng Xu; Jianmei Wu; Yuncheng Ji (Case Studies in Construction Materials)
Aiming to address the imbalance between ''sustainable advantages of environmental and cultural development'' and ''economic benefits'' in the development of rural wood structure architecture in China, as well as the disparity in development between traditional wood architecture and modern wood structure technology in rural areas, this study integrates modern wood structure technology while preserving traditional rural wood structure culture. A technical pathway for constructing a small log structure system aimed at enhancing timber efficiency and reducing structural costs is proposed. Through the research methods and processes of ''case analysis'' — ''multi-scheme comparison of creative group'' — ''SAP2000 structural system simulation'' — ''multi-factor comprehensive comparison'', the sustainable wood structure technical system suitable for the development of northeast China is explored. The main conclusions are as follows: firstly, two types of structural systems based on small-diameter round timber are proposed. These are composite component frame system and Lattice element structure system, which have good sustainability in terms of materials, construction methods and low-technology construction. Secondly, taking Northeast Larch of SDRT (a kind of small-diameter round timber tree species common in northeast China) as an example, the suitability space-threshold of its original wood properties in the structural systems can meet the needs of rural architectural space. Thirdly, compared to the LVL (laminated veneer lumber) frame structure system, the SDRT structure system can achieve a reduction in wood consumption per unit area ranging from 53.63 % to 75.87 % across various structural spans. Additionally, the cost of the building structure per unit area can be decreased by at least 45 %.